PENGARUH LEVEREGE, LIKUIDITAS, DAN FIRM SIZE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN TRANSPORTASI DAN LOGISTIK DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Simamora, Desnita Mawarni; Nasution, Ilham Ramadhan; Zulkarnaen, Zuliana (Worksheet : Jurnal Akuntansi, 2024)
This research analyzes the financial performance of transportation and logistics companies on the Indonesia Stock Exchange (BEI) for the 2018-2022 period, especially using the Return on Assets (ROA) ratio. Data shows that this industry experienced significant performance fluctuations during the COVID-19 pandemic, which caused a drastic decline in ROA in 2020. This research method uses a quantitative approach with multiple linear regression analysis to assess the influence of the leverage variable (Debt to Asset Ratio/DAR) , liquidity (Current Ratio/CR), and company size (Firm Size) on financial performance (ROA). The results of the descriptive analysis show that the variables leverage, liquidity and company size have a significant influence on ROA. The results of the F test state that the three independent variables simultaneously have a significant effect on financial performance. Partially, liquidity and company size have a significant positive effect on ROA, while leverage does not show a significant effect. This research provides important insights for company management in efforts to improve financial performance in the future